Pengaruh Hasil Tangkapan Ikan Tongkol (Euthynnus sp) dan Pendapatan Keluarga Nelayan Terhadap Tingkat Pendidikan Anak Keluarga Nelayan di Desa Seraya Timur, Kecamatan Karangasem, Kabupaten Karangasem - Apriantari, Ni Kadek; Dirgayusa, I Gusti Ngurah Putra; As-syakur, Abd. Rahman (Journal of Marine and Aquatic Sciences; Vol 3 No 2 (2017), 2017)
The East Seraya village has a potential of marines and fisheries, such as pelagic fish especially mackerel tuna fish according, production of tuna fish catch of 81% with the of catches 20.278,10 ton/year. Research on the effect of catch fish and income of fisherman family on education level of children of fisherman family have been done at Seraya village. Data were collected in each group of fishermen from January to February 2017. The sample was taken using simple random method, with 89 respondents. Methods for the analysis of the effect of tuna catch and family income of fishermen on education level of children of fishermen family using multinomial logistic regression analysis with software SPSS ( Statistical Package for Social Science. The educational level of the fishermen family has been completed at the level of fishermen children as follows; 2,2% for elementary school 14,6 % for junior high school, 33,7% for senior high school, 31,5 % for diploma, and 18,0%. Coefficient of R square determination Cox and Snell value is 0,940 which means that mackerel tuna fishing results and the fishermen incomes are simultaneous with the education level of fishermen children in the amount of 94%. Variable contribution of mackerel tuna fishing results (X1) which much affect the education level of fishermen children and the income of fishermen household (LnX2) affects the education level of fishermen children which is significant.